计算机断层扫描设备及其控制方法 (2016)
提供种计算机断层扫描设备及其控制方法。所述设备能够通过使用高速旋转的滤波器在高能量模式和低能量模式之间高速地切换。所述计算机断层扫描设备包括：X射线发生器，产生X射线并向对象照射X射线；X射线滤波器，包括至少个滤波器构件；驱动器，旋转X射线滤波器，以使滤波器构件选择性地被设置到X射线发生器产生的X射线的照射路径上；检测器，检测透过对象的X射线；主机设备，通过使用检测到的X射线获得X射线图像，基于透过相应的X射线的滤波器构件分离获得的X射线图像，并通过使用相同的滤波器构件的X射线图像来重构图像。 A computed tomography apparatus and a method for controlling the same are provided. The apparatus is capable of switching between a high energy mode and a low energy mode at a high speed using a filter that rotates at a high speed. The computed tomography apparatus includes an X-ray generator which generates and irradiates X-rays toward a subject, an X-ray filter which includes at least one filter member, a driver which rotates the X-ray filter such that the filter members are selectively disposed in an irradiation path of X-rays generated by the X-ray generator, a detector which detects the X-rays that are transmitted to the subject, and a host apparatus which obtains X-ray images by using detected X-rays, separates the obtained X-ray images based on filter membe